The Intergenic Interplay between Aldose 1-Epimerase-Like Protein and Pectin Methylesterase in Abiotic and Biotic Stress Control - Sheshukova, Ekaterina V.; Komarova, Tatiana V.; Pozdyshev, Denis V.; Ershova, Natalia M.; Shindyapina, Anastasia V.; Tashlitsky, Vadim N.; Sheval, Eugene V.; Dorokhov, Yuri L. (Frontiers in Plant Science, 2017)
The mechanical damage that often precedes the penetration of a leaf by a pathogen promotes the activation of pectin methylesterase (PME); the activation of PME leads to the emission of methanol, resulting in a “priming” effect on intact leaves, which is accompanied by an increased sensitivity to Tobacco mosaic virus (TMV) and resistance to bacteria. In this study, we revealed that mRNA levels of the methanol-inducible gene encoding Nicotiana benthamiana aldose 1-epimerase-like protein (NbAELP) in the leaves of intact plants are very low compared with roots. However, stress and pathogen attack increased the accumulation of the NbAELP mRNA in the leaves. Using transiently transformed plants, we obtained data to support the mechanism underlying AELP/PME-related negative feedback The insertion of the NbAELP promoter sequence (proNbAELP) into the N. benthamiana genome resulted in the co-suppression of the natural NbAELP gene expression, accompanied by a reduction in the NbAELP mRNA content and increased PME synthesis. Knockdown of NbAELP resulted in high activity of PME in the cell wall and a decrease in the leaf glucose level, creating unfavorable conditions for bacterial reproduction, which explains the reduced reproduction of Agrobacterium tumefaciens in injected leaves. Our results showed that NbAELP is capable of binding the TMV movement protein (MPTMV) in vitro and is likely to affect the cellular nucleocytoplasmic transport, which may explain the sensitivity of NbAELP knockdown plants to TMV. Although NbAELP was primarily detected in the cell wall, the influence of this protein on cellular PME mRNA levels might be associated with reduced transcriptional activity of the PME gene in the nucleus. To confirm this hypothesis, we isolated the N. tabacum PME gene promoter (proNtPME) and showed the inhibition of proNtPME-directed GFP and GUS expression in leaves when co-agroinjected with the NbAELP-encoding plasmid. We hypothesized that plant wounding and/or pathogen attack lead to PME activation and increased methanol emission, followed by increased NbAELP expression, which results in reversion of PME mRNA level and methanol emission to levels found in the intact plant.